Isu Perilaku Pendidikan pada Postingan Remaja Indonesia di Media Sosial Facebook - Alber, Alber; Asnawi, Asnawi; Wahyuni, Sri; Etfita, Fauzul; Andriana, Mella (GERAM: Gerakan Aktif Menulis, 2022)
This study aims to determine the phenomenon of educational behavior issues in posts by Indonesian youth on Facebook social media. This type of research uses qualitative methods with a phenomenological approach. The researcher chose to use this method with the consideration that the phenomena under study are phenomena that require the use of more profound observations and observations. The researcher wants to clearly describe the object of research through the phenomena experienced by related informants, namely youth posts on Facebook social media. In phenomenology's view, this study is based on state circumstances to give a naturalistic impression. This study found that Indonesian youth discussed many issues in the world of education on Facebook social media. Posts by Indonesian teenagers on Facebook prove that five main sub-themes form the basis of Indonesian youth's conversations regarding the education theme. The sub-themes in question are promotions, activities, assignments, speeches, and achievements